Flash journalism : - McAdams, Mindy (Focal Press, 2005)
This book will assist journalists and Flash developers who are working together to bring video, audio, still photos, and animated graphics together into one complete Web-based package. This book is not just another Flash book because it focuses on the need of journalists to tell an accurate story and provide accurate graphics. This book will illustrate how to animate graphics such as maps, illustrations, and diagrams using Flash. It will show journalists how to integrate high-quality photos and audio interviews into a complete news package for the Web.